TREATMENT OUTCOME OF TUBERCULOSIS CASES AMONG PAEDIATRIC PATIENTS IN WESTERN RAJASTHAN - YADAV, YOGESH; CHOUDHARY, JYOTI; KHAN, MOHAMMED NASIR (International Journal of Current Pharmaceutical Research, 2024)
Objective: This study aimed to identify drug-resistant tuberculosis cases and treatment results. Because it is one of the few studies that have looked at the results of TB treatment among children in the nation, this one was noteworthy. Methods: Drug-resistant cases of paediatric TB were recruited from various districts of Western Rajasthan. Drug resistance in Mycobacterium tuberculosis was detected by line Probe Assay. The cases were followed up for treatment. Results: A total of 41 drug-resistant TB cases were evaluated. Out of 41, 21 were rifampicin mono-resistant, 8 were isoniazid mono-resistant, MDR and pre-XDR were 5 each, and XDR cases were 2. 19 cases were successfully cured and there was one death reported during treatment. Conclusion: Cure rate of paediatric TB is less than 50% in our region. Adherence to treatment and contact isolation are crucial to increase cure rate and decrease the incidence of drug-resistant TB.